2023
DOI: 10.1007/s13204-023-02775-9
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of cationic dye on nanostructured biocarbons: kinetic and thermodynamic study

Abstract: Nanostructured bio-adsorbents were prepared by physical or chemical activation of the residue of supercritical extraction of raspberry seed. Their physicochemical properties were determined by elemental analysis, low-temperature nitrogen adsorption/desorption, Boehm titration and scanning electron microscopy. The biocarbon obtained as a result of physical activation of the precursor showed basic character of the surface and its SBET was 700 m2/g. The chemical activation of the residue of supercritical extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This may be explained by the presence of stronger centrifugal forces at 400 rpm/min, leading to repulsive forces between the dye molecules. When the repulsive forces exceed the binding force of the adsorbent, desorption of the dye begins [21,22] . The data presented suggests that optimum results for dye removal are achieved at a mixing speed of 300 rpm/min.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This may be explained by the presence of stronger centrifugal forces at 400 rpm/min, leading to repulsive forces between the dye molecules. When the repulsive forces exceed the binding force of the adsorbent, desorption of the dye begins [21,22] . The data presented suggests that optimum results for dye removal are achieved at a mixing speed of 300 rpm/min.…”
Section: Resultsmentioning
confidence: 86%
“…When the repulsive forces exceed the binding force of the adsorbent, desorption of the dye begins. [21,22] The data presented suggests that optimum results for dye removal are achieved at a mixing speed of 300 rpm/min. To optimise the results, a mixing speed of 300 rpm/min was selected for further investigation.…”
Section: Adsorption Of Methyl Redmentioning
confidence: 99%
“…Positive entropy values indicate increased randomness at the interface between the biochar and the solution of methylene blue/methyl red, which increases the effectiveness of removing the studied pollutants. The higher the value of ∆S 0 , the more efficient the process occurs [ 33 ]. Therefore, considering the results presented in Table 6 , it can be concluded that the most efficient adsorption process occurs for methylene blue and the PA7 sample.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is a possibility of π–π interactions occurring between the dye samples and aromatic rings. Comparable interactions have been documented and discussed in existing literature [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation